Posterior Reversible Leukoencephalopathy Syndrome (PRES) in a patient with post eclampsia with status epilepticus - Haleem, MA; Ishrat, -; Hamid, MA; Shuvon, - (Journal of Shaheed Suhrawardy Medical College, 2024)
Despite the limited number of instances and relatively low knowledge of Posterior Reversible Leukoencephalopathy Syndrome (PRES) among the population of Bangladesh, it is imperative to recognize the gravity of this health issue. The crucial aspect in achieving favorable results is the early detection of the condition, as it allows for the prompt elimination of the precipitating cause and the effective management of blood pressure. The present case study elucidates the significant discoveries pertaining to a patient with posterior reversible encephalopathy syndrome (PRES), as well as the diagnostic and therapeutic strategies used. A female individual who had just undergone a surgical operation known as a cesarean section exhibited symptoms including headache, recurrent convulsions, and loss of consciousness. Subsequent medical evaluation led to the diagnosis of posterior reversible encephalopathy syndrome (PRES). This section presents an examination of the diagnostic process using clinical and radiological characteristics, as well as an overview of the therapy plan. The fast diagnosis and timely beginning of therapy procedures have been identified as crucial factors for achieving early recovery and favorable functional outcomes. J Shaheed Suhrawardy Med Coll 2022; 14(2): 63-65